P5_6 Artificial Gravity for Kicks - Cook, Naomi Esther; Beedle, Thomas James; Baldwin, Emily Jane; Evershed, Mabel Elisabeth (Physics Special Topics, 2017)
In the film Inception, Arthur uses explosive devices to create artificial gravity in a zero-g dream. We estimate that the mass of TNT required to simulate gravitational acceleration on a lift containing six people is 11.6 kg. Finding that this is an unreasonable mass considering the size of the explosive devices in the film, we propose an alternative method requiring only 0.70 kg of TNT.